Kurikulum Langit dan Bumi: Strategi Integratif Pendidikan Islam Menjawab Tantangan Digital dan Globalisasi - Sangadah, Siti; Miftahurrohman, Miftahurrohman; Sukari, Sukari (Lembaga Yasin AlSys, 2026)
Islamic education in Indonesia plays a strategic role in shaping the nation’s character, morals, and spirituality, yet it faces multidimensional challenges both internally—including institutional management, curriculum quality, teacher professionalism, and financing—and externally in the form of globalization, sociocultural change, and the development of digital technology. This article aims to analyze these challenges and formulate relevant and sustainable development strategies for Islamic education. Using a qualitative research method through a literature study, the article reviews various books, scholarly articles, and policy documents related to Islamic education in Indonesia, globalization, and digital transformation. The findings indicate that Islamic education needs to implement an integrative curriculum that combines religious and general sciences, enhance teachers’ competencies along with their digital literacy, and revitalize educational institutions through professional management and innovative programs. In addition, the role of the community and stakeholders is crucial through financial support, collaboration in program development, and active involvement in students’ character formation. The article concludes that through integrative curriculum strategies, capacity building for teachers, digital literacy, institutional revitalization, and stakeholder support, Islamic education in Indonesia can remain adaptive to contemporary developments, remain rooted in Islamic values, and successfully nurture a generation that is knowledgeable, faithful, and of noble character.